دراسة مدى تأثير البكتيريا المعوية الموجودة في مجرى مياه الصرف الصحي على التربة الزراعية المحيطة بمدينة مسلاتة (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:In this study, the study area is the wastewater stream in the city of Msalata, which is located north of the capital city of Tripoli and the total number of 36 soil samples from the study points at a depth of 0-30 cm according to some criteria adopted in terms of some characteristics Chemical, and microbiological properties. E.coli , Salmonella and shigella bacteria, where samples were taken from the source deliver three replicates per point. The laboratory results obtained in this study show us:First, in terms of the microbiological aspect: it was noted that the bacteria Salmonella does not exist or exist in a small number of samples taken from the points that have been identified (5, 50, 100 meters) from east and west of the source, as well as shigella bacteria , but the bacteria E. Coli are present but in simple proportions, where most samples were less of 30 colonies in 100 ml of soil extract but are nevertheless harmful to plants and animals, indirectly affecting the food chain.
Keywords: wastewater stream; E.coli; Salmonella; shigella.